Tissue-specific study across the stem reveals the chemistry and transcriptome dynamics of birch bark - Alonso-Serra, Juan (2020)
Tree bark is a highly specialized array of tissues that plays important roles in plant protection and development. Bark tissues develop from two lateral meristems; the phellogen (cork cambium) produces the outermost stem-environment barrier called the periderm, while the vascular cambium contributes with phloem tissues. Although bark is diverse in terms of tissues, functions and species, it remains understudied at higher resolution. We dissected the stem of silver birch (Betula pendula) into eight major tissue types, and characterized these by a combined transcriptomics and metabolomics approach. We further analyzed the varying bark types within the Betulaceae family. The two meristems had a distinct contribution to the stem transcriptomic landscape. Furthermore, inter- and intraspecies analyses illustrated the unique molecular profile of the phellem. We identified multiple tissue-specific metabolic pathways, such as the mevalonate/betulin biosynthesis pathway, that displayed differential evolution within the Betulaceae. A detailed analysis of suberin and betulin biosynthesis pathways identified a set of underlying regulators and highlighted the important role of local, small-scale gene duplication events in the evolution of metabolic pathways. This work reveals the transcriptome and metabolic diversity among bark tissues and provides insights to its development and evolution, as well as its biotechnological applications.